(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the methodology of organizing extracurricular activities in general education schools, focusing on their pedagogical, psychological, and social significance. Extracurricular activities are regarded as an essential complement to formal education, providing opportunities for students to develop creativity, initiative, social responsibility, and moral values outside the classroom. The study emphasizes that properly organized extracurricular work strengthens students’ motivation, improves communication skills, and fosters cooperation between teachers, parents, and peers. Attention is given to the principles of planning, the role of the teacher as a mentor, and the integration of national traditions with modern pedagogical approaches. The article also analyzes challenges faced in extracurricular organization, such as limited resources, lack of methodological support, and uneven student participation, offering recommendations to enhance effectiveness. The outcomes of the study demonstrate that extracurricular activities are not only a form of leisure but also a powerful tool for the comprehensive development of students, contributing to their personal growth, civic consciousness, and academic success.